Values of Religious Moderation in Hindu Religious Education and Civil Lesson Materials at the High School Level in West Nusa Tenggara Indonesia - I Nyoman Wijana (Journal of Social Research, 2023)
This study aims to explore and describe the values of religious moderation contained in books on the subject matter of Hinduism and Moral Education at the senior high school level. The research used a qualitative approach, using interviews, observation, and documentation in data collection. The results of this study indicate that the values of religious moderation can be found in the syllabus, and also in the Hindu Religious Education and Moral Education textbooks at the senior high school level, including values; 1) accommodating to local culture and traditions, especially in subject matter: Yadnya, Wariga, Development of Hindu Culture, Tantra, Yantra, Mantra, 2) commitment to nationalism and love for the country, in subject matter: Upa Weda, Catur Warna, 3) tolerance and non-violence, on subject matter: Darsana, Catur Asrama, Yoga, Yama and Niyama Bratha, Sukhinah Family, Weda, Astangga Yoga. There was no subject matter containing anti-tolerance values, or subject matter that supported acts of violence in the  Hindu Religion and Moral High School textbooks.